2001
DOI: 10.2174/0929867013372535
|View full text |Cite
|
Sign up to set email alerts
|

Lipid, Sugar and Liposaccharide Based Delivery Systems

Abstract: Although there are formidable barriers to the oral delivery of biologically active drugs, considerable progress in the field has been made, using both physical and chemical strategies of absorption enhancement. A possible method to enhance oral absorption is to exploit the phenomenon of lipophilic modification and mono and oligosaccharide conjugation. Depending on the uptake mechanism targeted, different modifications can be employed. To target passive diffusion, lipid modification has been used, whereas the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…On the basis of these results, we postulate that bGal-NONOate is preferentially transported into cells through monosaccharide transporters on cell membranes. It has been reported that there are different types of monosaccharide transporters on the cell membrane such as sodium ion-dependent active transporter (SGLT1) and sodium ion-independent facilitative transporter (GLUT5), and attachment of one of monosaccharides transported by these transporters to drugs can increase the drug absorption [20]. These glycosylated conjugates tend to be accumulated inside cells according to the expression of specific hexose transporters on the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these results, we postulate that bGal-NONOate is preferentially transported into cells through monosaccharide transporters on cell membranes. It has been reported that there are different types of monosaccharide transporters on the cell membrane such as sodium ion-dependent active transporter (SGLT1) and sodium ion-independent facilitative transporter (GLUT5), and attachment of one of monosaccharides transported by these transporters to drugs can increase the drug absorption [20]. These glycosylated conjugates tend to be accumulated inside cells according to the expression of specific hexose transporters on the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that human tumor cells can overexpress one or more of these transporters [20]. However, in normal mammalian cells, there is no LacZ gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advances in physiological modeling and simulation of drug adsorption from the gastrointestinal tract, the fundamental process, which is the small intestinal transit flow, has not been characterized [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…LAAs combine the physico-chemical properties of both lipids and amino acids due to their amphipathic structure; LAAs linkage to drugs, apart from enhancing their lipophilicity, can also facilitate their interaction with cell membranes and penetration across absorption and biological barriers (8). Conjugation of drug molecules to lipoamino acids (LAA) has shown to increase biological uptake and intracellular concentration of drugs (8)(9)(10). The LAAs are also used to develop lipid core peptide systems useful for delivery of genes, drugs, and vaccines (11).…”
Section: Introductionmentioning
confidence: 99%